PEMANFAATAN SMARTPHONE DI ERA DIGITAL SEBAGAI MEDIA PEMBUATAN VIDEO PEMBELAJARAN BAGI GURU SD NEGERI 182 PALEMBANG - Meidyan Permata Putri; Eka Hartati; Muhammad Ridho Ardiansyah (Yayasan Education and Social Center, 2022)
In today's digital era, editors no longer need a professional camera to make videos to record quality images. KineMaster is a professional video editing application that is now popular among mobile device users. One of the features that YouTubers often use is the chroma key. Editing videos with KineMaster can be an alternative solution for beginners who are not very good at using video editing applications on a computer. Based on the results of interviews with Drs. Tugino, M.Pd.I as the Principal of the 182 Palembang State Elementary School, it is necessary to know that so far the material presented to students for making presentations uses a simple Microsoft Power Point application menu so that the results of the presentation of teacher assignments do not look attractive, therefore it is necessary held training on Smartphone Utilization in the Digital Age as a Media for Making Learning Videos for Teachers at SD Negeri 182 Palembang. This service activity is expected to provide knowledge and introduce the functions of the KineMaster application menus that can be used to make learning videos that are more interesting, more interactive and more fun. The method used in the delivery of service material is practice and question and answer. It is hoped that from the implementation of this activity the participants/teachers can make learning videos that are more interactive and fun